A review of visual aftereffects in schizophrenia. (June 2019) - Thakkar, Katharine N.; Silverstein, Steven M.; Brascamp, Jan W.
Highlights: Abnormal use of prior experience to interpret sensory information in schizophrenia. Visual aftereffects measure influence of prior experience on perception. Evidence for alterations of visual aftereffects in schizophrenia. Significant variability in findings due to type of aftereffect and clinical factors. Findings allow for mechanistic interpretations for altered visual aftereffects. Abstract: Psychosis—a cardinal symptom of schizophrenia—has been associated with a failure to appropriately create or use stored regularities about past states of the world to guide the interpretation of incoming information, which leads to abnormal perceptions and beliefs. The visual system provides a test bed for investigating the role of prior experience and prediction, as accumulated knowledge of the world informs our current perception. More specifically, the strength of visual aftereffects, illusory percepts that arise after prolonged viewing of a visual stimulus, can serve as a valuable measure of the influence of prior experience on current visual processing. In this paper, we review findings from a largely older body of work on visual aftereffects in schizophrenia, attempt to reconcile discrepant findings, highlight the role of antipsychotic medication, consider mechanistic interpretations for behavioral effects, and propose directions for future research.